Impatiens meishanensis (Balsaminaceae), a new species from Sichuan, China - Yanru Zhang; Xinyu Chen; Tianmeng Qu; Xinyi Zheng; Bo Li; Jieli Yue; Xiaoqin Liu; Min Pan; Ke Huang; Zhixi Fu (PhytoKeys, 2025)
Impatiens meishanensis K.Huang & Z.X.Fu, sp. nov., a new species of Balsaminaceae from Meishan City, Sichuan Province, China, is described and illustrated. The complete chloroplast (cp) genome of I. meishanensis is 152,104 bp in length. Based on phylogenetic analysis of the complete cp genome, I. meishanensis represents a distinct species closely related to Impatiens faberi Hook.f. The new species can be distinguished from the latter by its unique morphological characteristics: lower sepal gable-boat-shaped (vs. funnel-shaped), spur straight (vs. curved), flower large, ca. 4 cm long (vs. ca. 3 cm long), and seeds ellipsoid with reticulate seed coat ornamentation (vs. oblong, smooth). In addition, a distribution map, a detailed morphological comparison with related species, and an assessment of the conservation status of this newly identified species are provided.